2020
DOI: 10.1101/2020.03.16.20037168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Roles of meteorological conditions in COVID-19 transmission on a worldwide scale

Abstract: The novel coronavirus (SARS-CoV-2/ 2019-nCoV) identified in Wuhan, China, in December 2019 has caused great damage to public health and economy worldwide with over 140,000 infected cases up to date. Previous research has suggested an involvement of meteorological conditions in the spread of droplet-mediated viral diseases, such as influenza. However, as for the recent novel coronavirus, few studies have discussed systematically about the role of daily weather in the epidemic transmission of the virus. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
172
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 11 publications
6
172
3
7
Order By: Relevance
“…Several recent reports have also linked higher temperature to decreased virus spread, while others have found no significant effects. [9][10][11][12][13][14] Here, we demonstrate an independent effect of temperature that results in reduced COVID-19 cases, but not mortality, across U.S. counties. If warmer temperatures do, in fact, play a role in mitigating disease spread, it is reasonable to expect a potential seasonal trend in global cases and mortality.…”
Section: Impact Of Temperaturementioning
confidence: 88%
See 2 more Smart Citations
“…Several recent reports have also linked higher temperature to decreased virus spread, while others have found no significant effects. [9][10][11][12][13][14] Here, we demonstrate an independent effect of temperature that results in reduced COVID-19 cases, but not mortality, across U.S. counties. If warmer temperatures do, in fact, play a role in mitigating disease spread, it is reasonable to expect a potential seasonal trend in global cases and mortality.…”
Section: Impact Of Temperaturementioning
confidence: 88%
“…Recent work has primarily focused on patient demographics, underlying health comorbidities, social disparities in healthcare access and quality, and environmental variables such as pollution to identify potential risk factors and vulnerable populations. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, while these previous studies have examined the effects of these domains on COVID-19 spread independently, some do not control for the potentially confounding interactions between variables. In this study, we sought to investigate COVID-19 prevalence and mortality in all U.S. counties through a more comprehensive framework that accounts for effects of county-level macroeconomic, demographic, environmental, health status, and healthcare access variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These empirical frameworks conflate location-specific characteristics -such as testing capacity, population density, and health services -with temperature variation. [8][9][10] Because temperature is correlated with many (often unobservable) confounding factors, such cross-sectional comparisons may not have a causal interpretation. [11][12][13] For example, countries that are cooler on average also tend to have higher income per capita 14 which may affect the number of new COVID-19 cases by enabling more public health measures such as testing and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…We modeled with a hierarchical Bayesian Gaussian regression with a log link on the weekly in previous studies (11)(12)(13). Based on sensitivity analyses discussed below, we found that 382 maximum daily UV was a considerably better predictor than the mean (delta LOOIC = 4.x) so 383 we used the maximum in our best model.…”
mentioning
confidence: 99%